Flint Hills Farm Ponds: Good, Bad, But Rarely Ugly - Tim Keane (Symphony in the Flint Hills, 2018)
Introduction: Stand atop any ridge in the Flint Hills of Kansas in late spring and look about. The fires are finished, the prairie is a new and vibrant green, and the black and russet daubs that amble in the distance are the cattle returned to summer range. Regardless of the direction you gaze from that cuesta, you will likely see at least one farm or stock pond. These ponds, an estimated quarter million of them in Kansas, built by farmers and ranchers over the last hundred years or so, provide water for cattle, but so much more.